GENERAL PRINCIPLES OF A FREE SOCIETY FOR SPONTANEOUS ORDER TO STRENGTHEN THE MARKET - Rodríguez Cairo, Vladimir (2015)
This study addresses the general principles of a free society referring to the tradition of individual freedom, justice and limited government. It seeks to answer the question: Why does the spontaneous market order require the vindication of those principles?In that regard, it should be noted that the nature of the study is of explanatory type. Thus, the research method used is analytical. Similarly, the literature sources which support the essential principles of a free society and the spontaneous market order were consulted.For a better understanding of the proposed theme, the content is structured in three parts. The first comprises the background. In the second the spontaneous market order is explained. The third covers the general prin-ciples of a free society. Then the conclusions. Finally, the literature is mentioned.